2022
DOI: 10.1039/d1tc04834a
|View full text |Cite
|
Sign up to set email alerts
|

Highly efficient triplet–triplet annihilation upconversion in polycaprolactone: application to 3D printable architectures and microneedles

Abstract: This research reports the next generation of solid-state triplet–triplet annihilation upconversion (TTA-UC) host material (polycaprolactone, PCL) for highly efficient, processable, and biocompatible solid-state TTA-UC. UC PCL was successfully fabricated using...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…216 Its excellent biocompatibility, thermoplasticity, and strong mechanical stability makes it suitable for a wide range of biomedical applications, such as 3D-printed UC microneedles. 216 Furthermore, Turshatov et al observed efficient solid-state TTA-UC well below T g when using amorphous poly(olefin sulfone)s as host materials which also act as an excellent oxygen barrier. 217 This group of materials behaves more fluidically at the nanoscale and more rigid at the macroscale due to the incorporation of long flexible side chains, thereby showing great promise for the use of integrating solidstate TTA-UC.…”
Section: Polymeric Matricesmentioning
confidence: 99%
See 2 more Smart Citations
“…216 Its excellent biocompatibility, thermoplasticity, and strong mechanical stability makes it suitable for a wide range of biomedical applications, such as 3D-printed UC microneedles. 216 Furthermore, Turshatov et al observed efficient solid-state TTA-UC well below T g when using amorphous poly(olefin sulfone)s as host materials which also act as an excellent oxygen barrier. 217 This group of materials behaves more fluidically at the nanoscale and more rigid at the macroscale due to the incorporation of long flexible side chains, thereby showing great promise for the use of integrating solidstate TTA-UC.…”
Section: Polymeric Matricesmentioning
confidence: 99%
“…For instance, polycaprolactone (PCL) has a low T g (ca. −60 °C) while exhibiting low oxygen permeability . Its excellent biocompatibility, thermoplasticity, and strong mechanical stability makes it suitable for a wide range of biomedical applications, such as 3D-printed UC microneedles .…”
Section: Solid-state Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In consequence, to develop solid-state TTA-UC with high efficiency and good processability has always been a research hotspot. 62 To pursue this aim, many types of soft matters, including organogel, hydrogel, microcapsule, nanoparticle and polymer film, were reported as solid-state TTA-UC carriers, [63][64][65] which exhibited solid form at macroscopic scale and kept liquid state at microscopic scale. Whereas, few research works have focused on the processability of solid-state TTA-UC.…”
Section: Resultsmentioning
confidence: 99%
“…Compared with thermally initiated free‐radical reactions, photoinitiated ones have advantages of low‐energy consumption and fast reaction velocity. [ 1,4,5 ] Besides, with their superiorities of controllable space, low equipment requirement, [ 1,6 ] and environmental friendliness, [ 7 ] photoinitiated reactions are extensively used in the fields of coatings, adhesives, [ 8 ] optoelectronics, 3D printing, [ 9,10 ] nanotechnology, etc.…”
Section: Introductionmentioning
confidence: 99%